On the Seismic Performance of the Single-Layer Reticulated Shell with a Center-Hung Scoreboard under Multiple Seismic Excitations - Renjie Liu; Ce Ji; Xiongyan Li; Chao Wang; Guangyong Wang (Shock and Vibration, 2023)
Single-layer reticulated shells are widely used as roof structures of gymnasiums. However, the seismic performance of the single-layer reticulated shell with a center-hung scoreboard (CHS), which is a kind of large-scale display device suspended on the roof center of many gymnasiums, has not been fully studied. In this paper, the influence of the CHS on the seismic response of single-layer reticulated shells is investigated. Single-layer reticulated shells and the CHS-integrated models including flexibly suspended models and simplified models are established, respectively, using the Abaqus software. The responses of integrated models are calculated by an explicit dynamic method under 3D seismic action. The axial forces of the flexibly suspended case and the simplified case where the scoreboard is simplified as fixed masses on the roof structure are compared. Compared with those in the simplified model, the axial forces of some shell members and some nodal acceleration in the flexibly suspended model under multiple seismic excitations would increase by as high as 125% and 315%, respectively. It turns out that seismic responses of the single-layer reticulated shell would be underestimated if a simplified model was used for seismic response analysis. The region near the boundary and the region neighbouring the support platform members are the most affected regions due to the combination of the horizontal swing effect and the vertical impact effect of the CHS under multiple seismic excitations.